Hadith #210 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) ate (a piece of) mutton from the shoulder region and then prayed without repeating the ablution.
Grade: Sahih

Hadith #235 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) was asked regarding ghee (cooking butter) in which a mouse had fallen. He said, “Take out the mouse and throw away the ghee around it and use the rest.”
Grade: Sahih

Hadith #236 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) was asked regarding ghee in which a mouse had fallen. He said, “Take out the mouse and throw away the ghee around it (and use the rest.)”
Grade: Sahih

Hadith #249 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
(the wife of the Prophet) Allah’s Messenger (ﷺ) performed ablution like that for the prayer but did not wash his feet. He washed off the discharge from his private parts and then poured water over his body. He withdrew his feet from that place (the place where he took the bath) and then washed them. And that was his way of taking the bath of Janaba.
Grade: Sahih

Hadith #257 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
I placed water for the bath of the Prophet. He washed his hands twice or thrice and then poured water on his left hand and washed his private parts. He rubbed his hands over the earth (and cleaned them), rinsed his mouth, washed his nose by putting water in it and blowing it out, washed his face and both forearms and then poured water over his body. Then he withdrew from that place and washed his feet.
Grade: Sahih

Hadith #259 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
I placed water for the bath of the Prophet (ﷺ) and he poured water with his right hand on his left and washed them. Then he washed his private parts and rubbed his hands on the ground, washed them with water, rinsed his mouth and washed his nose by putting water in it and blowing it out, washed his face and poured water on his head. He withdrew from that place and washed his feet. A piece of cloth (towel) was given to him but he did not use it.
Grade: Sahih

Hadith #260 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) took the bath of Janaba. (sexual relation or wet dream). He first cleaned his private parts with his hand, and then rubbed it (that hand) on the wall (earth) and washed it. Then he performed ablution like that for the prayer, and after the bath he washed his feet.
Grade: Sahih

Hadith #265 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
I placed water for the bath of Allah’s Messenger (ﷺ) and he poured water over his hands and washed them twice or thrice; then he poured water with his right hand over his left and washed his private parts (with his left hand). He rubbed his hand over the earth and rinsed his mouth and washed his nose by putting water in it and blowing it out. After that he washed his face, both fore arms and head thrice and then poured water over his body. He withdrew from that place and washed his feet.
Grade: Sahih

Hadith #266 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
I placed water for the bath of Allah’s Messenger (ﷺ) and put a screen. He poured water over his hands, and washed them once or twice. (The sub-narrator added that he did not remember if she had said thrice or not). Then he poured water with his right hand over his left one and washed his private parts. He rubbed his hand over the earth or the wall and washed it. He rinsed his mouth and washed his nose by putting water in it and blowing it out. He washed his face, forearms and head. He poured
Grade: Sahih

Hadith #273 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
Water was placed for the ablution of Allah’s Messenger (ﷺ) after Janaba. He poured water with his right hand over his left twice or thrice and then washed his private parts and rubbed his hand on the earth or on a wall twice or thrice and then rinsed his mouth, washed his nose by putting water in it and then blowing it out and then washed his face and forearms and poured water over his head and washed his body. Then he shifted from that place and washed his feet. I brought a piece of cloth,
Grade: Sahih

Hadith #275 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
I placed water for the bath of the Prophet (ﷺ) and screened him with a garment. He poured water over his hands and washed them. After that he poured water with his right hand over his left and washed his private parts, rubbed his hands with earth and washed them, rinsed his mouth, washed his nose by putting water in it and then blowing it out and then washed his face and forearms. He poured water over his head and body. He then shifted from that place and washed his feet. I gave him a piece of
Grade: Sahih

Hadith #280 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
I screened the Prophet (ﷺ) while he was taking a bath of Janaba. He washed his hands, poured water from his right hand over his left and washed his private parts. Then he rubbed his hand over a wall or the earth, and performed ablution similar to that for the prayer but did not wash his feet. Then he poured water over his body, shifted from that place, and washed his feet.
Grade: Sahih

Hadith #300 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
When ever Allah’s Messenger (ﷺ) wanted to fondle any of his wives during the periods (menses), he used to ask her to wear an Izar.
Grade: Sahih

Hadith #329 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
(the wife of the Prophet) During my menses, I never prayed, but used to sit on the mat beside the mosque of Allah’s Messenger (ﷺ). He used to offer the prayer on his sheet and in prostration some of his clothes used to touch me.”
Grade: Sahih

Hadith #377 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) used to pray on Khumra.
Grade: Sahih

Hadith #508 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
My bed was beside the praying place (Musalla) of the Prophet (ﷺ) and sometimes his garment fell on me while I used to lie in my bed.
Grade: Sahih

Hadith #509 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) used to pray while I used to sleep beside him during my periods (menses) and in prostration his garment used to touch me.
Grade: Sahih

Hadith #1918 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The people doubted whether the Prophet (ﷺ) was fasting on the day of `Arafat or not, so I sent milk while he was standing at `Arafat, he drank it and the people were looking at him.
Grade: Sahih

Hadith #2678 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Last night two men came to me (in a dream) and made me ascend a tree and then admitted me into a better and superior house, better of which I have never seen. One of them said, ‘This house is the house of martyrs.”
Grade: Sahih

Hadith #3103 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) said, “Last night I saw (in a dream) two men coming to me. One of them said, “The person who kindles the fire is Malik, the gate-keeper of the (Hell) Fire, and I am Gabriel, and this is Michael.”
Grade: Sahih

Hadith #3216 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “Two persons came to me at night (in dream) (and took me along with them). We passed by a tall man who was so tall that I was not able to see his head and that person was Abraham.”
Grade: Sahih

Hadith #5325 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
A mouse fell into the butter-fat and died. The Prophet (ﷺ) was asked about that. He said, “Throw away the mouse and the butter-fat that surrounded it, and eat the rest of the butter-fat (As-Samn).
Grade: Sahih

Hadith #5327 - Sahih al-Bukhari - Maimuna (Sahih al-Bukhari)
The Prophet (ﷺ) was asked about a mouse that had fallen into butter-fat (and died). He said, “Throw away the mouse and the portion of butter-fat around it, and eat the rest.”
Grade: Sahih